37th Annual Hawaii International Conference on System Sciences, 2004. Proceedings of The 2004
DOI: 10.1109/hicss.2004.1265287
|View full text |Cite
|
Sign up to set email alerts
|

Digital artifacts for remembering and storytelling: posthistory and social network fragments

Abstract: Visualizations of the patterns in email archives are powerful catalysts for personal storytelling. As part of a long-term investigation into visualizing email, we have created two visualizations of email archives.One highlights social networks while the other depicts the temporal rhythms of interactions with individuals. In our interviews with users of these systems, one of the most striking and not entirely expected comments was that using the applications triggered recall of many personal events and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 8 publications
2
90
0
2
Order By: Relevance
“…These displays are seen by thousands and it is natural to ask what new opportunities arise when visualizations move to an environment where vast crowds of people can create, view and discuss them. Not only are interactive visualizations a key medium for communication in a data-rich world, but preliminary reports hint that visualizations potentially have a catalytic effect on storytelling [26] and collective data analysis [28].…”
Section: Introductionmentioning
confidence: 99%
“…These displays are seen by thousands and it is natural to ask what new opportunities arise when visualizations move to an environment where vast crowds of people can create, view and discuss them. Not only are interactive visualizations a key medium for communication in a data-rich world, but preliminary reports hint that visualizations potentially have a catalytic effect on storytelling [26] and collective data analysis [28].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they become available for reflection and discussion. Viégas et al (2004) revealed the impact of visualizing the e-mail history for the participants in e-mail conversations: Their visualization of evolving social relationships, made visible from email exchanges, prompted users to tell stories about their social network. At present, there are first attempts to foster self-reflective storytelling by visualizing artifacts based upon activities in social networks (Zalinger 2009).…”
Section: Applications Of Storytelling In Educationmentioning
confidence: 99%
“…The timeline, besides providing an overall perception of all the listening history, guides the user while exploring his/her listening history. In the doted visualization, much like what Viégas did in [20] and [21], each stacked dots bar encode a time interval of the selected time period, and each dot represents a data element (artist, album or track) listened in that interval. For example, in Figure 1, each column represents a day, and each dot an artist listened in that day.…”
Section: Visual Designmentioning
confidence: 99%
“…The work by Viégas et al partially inspired MULHER: PostHistory [20] and Themail [21] provide chronological insights into communication patterns. Reminiscing and making sense of the past are central activities in both approaches.…”
Section: General Information Visualizationmentioning
confidence: 99%